Making good citizens : education and civil society - Ravitch, Diane; Viteritti, Joseph P., 1946- (Yale University Press, 2001)
Americans have reason to be concerned about the condition of American democracy at the start of the twenty-first century. Surveys show that civic participation has declined, cynicism about government has increased, and young people have a weak grasp of the principles that underlie our constitutional system. Crucial questions must be answered: How serious is the situation? What role do schools play in shaping civic behaviour? Are current education reform initiatives, such as multiculturalism and school choice, counterproductive? How can schools contribute toward reversing the trend? This volume brings together leading thinkers from a variety of disciplines to probe the relation between a healthy democracy and education. Their original and provocative discussions cut across a range of important topics: the cultivation of democratic values, the formation of social capital in schools and communities, political conflict in a pluralist society, the place of religion in public life, the enduring problems of racial inequality. Gathering together the most recent research and thinking on education and civil society, this is a book that deserves the attention of everyone who cares about the quality and future of American democracy.
Keywords: Citizenship -- Study and teaching -- United States.; Civics -- Study and teaching -- United States.; Education -- Aims and objectives -- United States.; Éducation à la citoyenneté -- États-Unis.; Éducation -- Finalités -- États-Unis.; Citoyenneté -- Étude et enseignement -- États-Unis.; EDUCATION -- Aims & Objectives.; EDUCATION -- Philosophy & Social Aspects.; Citizenship -- Study and teaching; Civics -- Study and teaching; Education -- Aims and objectives; United States; Onderwijs.; Doelstellingen.; Burgerschap.; Democratie.; Politieke socialisatie.